Etika Profesi Notaris dalam Perspektif Hukum - Asfariyani A. Talango; Roy Marthen Moonti; Ibrahim Ahmad (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Notary professional ethics plays an important role in maintaining integrity and public trust in notary practice. This research aims to analyze the regulation of notary professional ethics in the Indonesian legal system and explain the sanctions imposed on violations of these ethics in the practice of notary office. The research method used is the normative juridical method with a statutory approach. The results show that the regulation of notary professional ethics in Indonesia is regulated in Law Number 30 of 2004 concerning the Notary Position which has been amended by Law Number 2 of 2014, as well as the Notary Code of Ethics issued by the Indonesian Notary Association (INI). Violations of professional ethics may be subject to sanctions in the form of reprimand, writing, respectful dismissal, to dishonorable dismissal according to the level of violation. The enforcement of these sanctions aims to maintain professionalism and ensure legal protection for parties using notary services. This study recommends strengthening supervision of the implementation of the code of ethics and increasing education to notaries to prevent violations.